Magnetic nanocatalyst for microwave-assisted synthesis of Benzo[4,5]imidazo[1,2-a]pyrimidines via A3 coupling - Pan, Yuqiang (Frontiers in Chemistry, 2025)
This manuscript introduces an innovative and environmentally benign magnetic nanocatalyst (NiFe2O4@MCM-41@IL/Pt(II)) designed to synthesize benzoimidazo[1,2-a]pyrimidines via a microwave-assisted, one-pot A3 coupling reaction. The methodology employs aromatic and heteroaromatic aldehydes, 2-aminobenzimidazole derivatives, and terminal alkynes in water as a green solvent, leveraging the synergistic effects of nanocatalysis and microwave irradiation. The magnetic nanocatalyst, characterized by its robust structure and high surface reactivity, facilitates rapid reaction kinetics, achieving excellent yields while significantly reducing energy consumption and reaction time compared to conventional thermal approaches. Its inherent magnetic properties enable straightforward separation and reuse across multiple cycles without appreciable loss in catalytic efficiency, aligning with sustainable chemistry principles. The protocol demonstrates broad substrate compatibility, successfully accommodating diverse aldehydes, including challenging heteroaromatic systems, to furnish a library of pharmaceutically relevant heterocycles. This broad substrate compatibility underscores the versatility of the nanocatalyst, making it a valuable tool for a wide range of chemical synthesis applications. This work highlights the transformative role of hybrid methodologies in addressing both efficiency and environmental impact in chemical synthesis.